Sequence variation in mature microRNA-608 and benefit from neo-adjuvant treatment in locally advanced rectal cancer patients. (5th July 2016) - Sclafani, Francesco; Chau, Ian; Cunningham, David; Lampis, Andrea; Hahne, Jens Claus; Ghidini, Michele; Lote, Hazel; Zito, Domenico; Tabernero, Josep; Glimelius, Bengt; Cervantes, Andres; Begum, Ruwaida; et al.
Summary: Analysis of a polymorphism in mature microRNA-608 (rs4919510) in rectal cancer patients enrolled in a randomized phase II clinical trial identified patient subpopulations who might benefit from the use of an intensified neo-adjuvant treatment strategy with Cetuximab. Abstract : Single nucleotide polymorphisms (SNPs) in microRNA genes have been associated with colorectal cancer (CRC) risk, survival and response to treatment. Conflicting results are available on the association between rs4919510, a SNP in mature miR-608 and clinical outcome in CRC. Here, we analyzed the association between rs4919510 and benefit from perioperative treatment in a randomised phase II trial of neoadjuvant Capecitabine and Oxaliplatin (CAPOX) followed by chemo-radiotherapy, surgery and adjuvant CAPOX ± Cetuximab in high-risk locally advanced rectal cancer (LARC). A total of 155/164 (94.5%) patients were assessable. 95 (61.3%) were homozygous for CC, 55 (35.5%) heterozygous (CG) and 5 (3.2%) homozygous for GG. Median follow-up was 64.9 months. In the CAPOX arm the 5-year progression-free survival (PFS) and overall survival (OS) rates were 54.6% and 60.7% for CC and 82.0% and 82.1% for CG/GG, respectively (HR PFS 0.13, 95% CI: 0.12–0.83, P = 0.02; HR OS 0.38, 95% CI: 0.14–1.01, P = 0.05). In the CAPOX-C arm PFS and OS were 73.2 and 82.2%, respectively for CC carriers and 64.6 and 73.1% for CG/GG carriers (HR PFS 1.38, 95% CI: 0.61–3.13, P = 0.44; HR OS 1.34, 95% CI: 0.52–3.48, P = 0.55). An interaction was found between study treatment and rs4919510 genotype for both PFS ( P = 0.02) and OS ( P = 0.07). This is the first study investigating rs4919510 in LARC. The CC genotype appeared to be associated with worse prognosis compared to the CG/GG genotype in patients treated with chemotherapy and chemo-radiotherapy alone. Addition of Cetuximab to chemotherapy and chemo-radiotherapy in CC carriers appeared to improve clinical outcome.